2011
DOI: 10.1021/jp2056305
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Chlorine K-Edge XANES Spectra During the Breakdown of Passive Oxide Films on Aluminum

Abstract: We generated molecular simulations of Cl– interacting at different sites in aluminum oxide models and carried out FEFF8 calculations to obtain the local l-projected density of states (LDOS) spectra. These are compared to our earlier experimental X-ray absorption near-edge structure (XANES) data in order to study the interactions of chloride ions with the passive oxide film on aluminum as a function of electrochemical potential at the Cl K edge. This led to a number of new insights in the mechanism of the break… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…The modeling work by O'Grady et al 79 show Cl − within the oxide and at the oxide metal/interface at potentials below E pit . These experimental and modeling data, in the view of the authors, present a very compelling case that Cl − is incorporated in the entirety of the oxide film at the potentials studied below and above E pit and that Cl − moves through the oxide film.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The modeling work by O'Grady et al 79 show Cl − within the oxide and at the oxide metal/interface at potentials below E pit . These experimental and modeling data, in the view of the authors, present a very compelling case that Cl − is incorporated in the entirety of the oxide film at the potentials studied below and above E pit and that Cl − moves through the oxide film.…”
Section: Discussionmentioning
confidence: 99%
“…The The XANES data recorded at -0.850 V sce were compared to the theoretically calculated LDOS spectrum for four possible oxygen positions. 79 The theoretical LDOS for Cl − in the recessed site was compared with the XANES data shown in Figure 14. Of the 4 possibilities, this simulation yielded the best fit of the calculated spectrum with the actual data.…”
Section: Experimental Evidence For Chloride Incorporation In the Oxidmentioning
confidence: 99%
“…The formation and corrosion protection mechanism of the metal cation layer of Zn 2+ is detailed in Figure A and B. Several studies have reported that an Al 2 O 3 layer (5‐ to 10‐nm thickness) is formed on aluminum alloys and that the layer has OH − sites at the solution/Al 2 O 3 interface . Hard and soft acids and bases (HSAB) theory has reported that hard acids and hard bases form strong bonds .…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have reported that an Al 2 O 3 layer (5-to 10-nm thickness) is formed on aluminum alloys 10,12 and that the layer has OH − sites at the solution/Al 2 O 3 interface. 13,14 Hard and soft acids and bases (HSAB) theory has reported that hard acids and hard bases form strong bonds. 15,16 Commonly, Zn 2+ is categorized as a hard acid and OH − as a hard base; from this, it may be proposed that Zn 2+ easily bonds with the OH − on the Al 2 O 3 layer on aluminum alloys ( Figure 6A).…”
Section: Formation and Corrosion Protection Mechanism Of Metal Catimentioning
confidence: 99%
“…X-ray Photoemission Spectroscopy (XPS) measurements supported by DFT calculations of core electron spectra have made a convincing case that this substitution, without electron transfer, takes place on oxide-passivated Al metal surfaces. [51][52][53][54] Computationally, fluorination of AlOH groups using HF gas has been predicted to be energetically favorable. [62][63][64] In this work, we report DFT energetics associated with Cl − →OH − on the α-Al 2 O 3 (0001) surface using parameters consistent with those we apply to examine Cl − insertion into V O inside the oxide film, so that a comparison of mechanisms can be made.…”
Section: Introductionmentioning
confidence: 99%